Corresponding directions line surfaces of line hypercomplex in multidimensional affine space - Jadvyga Vainavičienė (Lietuvos Matematikos Rinkinys)
In this article the study of line hypercomplex in n-dimensional affine space An is continued (see [1]). There are found some algebraic hypersurfaces and correspondence between the normal spaces. The geometrical interpretations of some geometric objects are given.